THE DISABLED GOD toward a Liberatory Theology of Disability - Eiesland, Nancy L. (Nashville ABindon Press, 1994)
Integrating intellectual with personal, political and spiritual, the author defines a liberatory theology for the disabled.
Keywords: 1.Church work with the handicapped; 2.Body,human-Religious aspects-christianity.; 3. Theology-forercasting.